Comparison Between Simple Round Robin and Improved Round Robin Algorithms - Tri Dharma Putra; Rakhmat Purnomo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The objective of this journal is to compare the efficiency between these two algorithms, the simple round robin and improved round robin algorithms. In real time systems algorithm, round robin plays a significant role to be used in embedded systems. Here we compare the average turn around time and average waiting time, also number of context switching between these two algorithms. Improved round robin algorithm, is an algorithm where if the remaining burst time is less than the allocated time quantum then the running process is executed. Then remove the currently running process from ready queue and put it in the tail of the ready queue while in simple round robin algorithm the remaining burst time will be executed until finish as scheduled. This comparison proves that improved round robin algorithm is more efficient, with lower average turn around time and lower average waiting time, lower context switching. There by this increases the system throughput.